Автоматизація синхронізованого руху автономних систем діагностики за допомогою мереж Петрі та алгоритму RRT* - Проценко, А. А. (ХНУРЕ, 2024)
In the modern world, autonomous diagnostic systems are used to solve various tasks in complex conditions, including underground structures, where conventional navigation methods may be inadequate due to limited availability of environmental information. In this work, we will consider a pathfinding system based on the RRT* algorithm and its integration with Petri nets for automating synchronized movement of autonomous diagnostic systems.
Keywords: система діагностики; автоматизація синхронізованого руху